Improvement in gait function after carotid endarterectomy is associated with postoperative recovery in perfusion and neurotransmitter receptor function in the motor-related cerebral cortex: a 123I-iomazenil SPECT study. Issue 11 (November 2020) - Sato, Shinpei; Fujiwara, Shunrou; Miyoshi, Kenya; Chida, Kohei; Kobayashi, Masakazu; Kubo, Yoshitaka; Yoshida, Kenji; Terasaki, Kazunori; Ogasawara, Kuniaki
Abstract : Objective: Carotid endarterectomy (CEA) often restores cerebral perfusion and neurotransmitter receptor function, which is seen on early and late images, respectively, on brain 123 I-iomazenil single-photon emission computed tomography (SPECT). The reliability of gait-related parameters obtained using a triaxial accelerometer, a portable device for gait assessment, has been confirmed with test-retest measurements. The purpose of the present prospective cohort study was to determine whether improvement in gait function after CEA is associated with postoperative recovery in perfusion and neurotransmitter receptor function in the motor-related cerebral cortex. Methods: Gait testing using a triaxial accelerometer was performed preoperatively and 6 months postoperatively in 64 patients undergoing CEA for ipsilateral internal carotid artery stenosis (≥70%). 123 I-iomazenil SPECT was also performed with scanning within 30 min (early images) and at 180 min (late images) after tracer administration before and after surgery. SPECT data were analyzed using a three-dimensional stereotactic surface projection, and motor (Brodmann 4) and premotor (Brodmann 6) cortexes in each hemisphere were combined and defined as the motor-related cortex. Results: Based on preoperative and postoperative gait testing, seven patients (11%) showed postoperative improved gait. Logistic regression analysis revealed that postoperative increase in 123 I-iomazenil uptake in the motor-related cortex ipsilateral to surgery on early [95% confidence interval (CI), 4.32–365.21; P  = 0.0477) or late (95% CI, 9.45–1572.57; P  = 0.0173) images was an independent predictor of postoperative improved gait. Conclusions: Improvement in gait function after CEA is associated with postoperative recovery in perfusion and neurotransmitter receptor function in the motor-related cerebral cortex.